ASSESSMENT OF ANTIMICROBIAL PROPERTIES AND CYTOTOXICITY EFFECTS OF HERBAL GEL FORMULATION USING LAGENARIA SICERARIA (BOTTLE GOURD) FORTIFIED WITH HONEY FOR TREATING ORAL ULCERS- AN IN VITRO STUDY. - Sidharth Erramshetty; Jayashri Prabakar; Meignana Arumugham Indiran; Rajesh Kumar Shanmugham (Romanian Society of Oral Rehabilitation, 2024)
Introduction: Oral ulcers are a common, painful condition with limited effective treatment options. This study explores the potential of a novel herbal gel formulation using Lagenaria siceraria (Bottle gourd) fortified with honey as a treatment for oral ulcers. Materials and methods: The gel's antimicrobial and cytotoxic activities were evaluated in vitro. Lagenaria siceraria was extracted and combined with honey to create the gel, which was tested against three bacterial strains: Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa using agar well diffusion and time-kill curve assays. Results: The results demonstrated significant antimicrobial activity, with the highest inhibition observed in P. aeruginosa. Cytotoxicity was assessed using nauplii fish, showing minimal adverse effects at lower concentrations. Conclusion: This study suggests that the Lagenaria siceraria and honey gel could be a promising, natural alternative for managing oral ulcers, combining efficacy with low cytotoxicity. Further studies are recommended to validate these findings and explore the potential for clinical application.